2021
DOI: 10.3390/agronomy11101963
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Opuntia ficus-indica Mucilage Edible Coating on Quality, Nutraceutical, and Sensorial Parameters of Minimally Processed Cactus Pear Fruits

Abstract: Cactus pear (Opuntia ficus-indica (L.) Mill.) is a non-climacteric fruit with a relatively short postharvest life span, being very sensitive to water loss, darkening and decay. Cactus pear is a spiny fruit, and the presence of glochids limits fruit consumption and diffusion; therefore, minimally processing, as well as peel removing, could be an opportunity to improve its availability, consumption, and diffusion in national and international markets. In this study, cactus pear minimally processed fruits were tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

20
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(55 citation statements)
references
References 42 publications
20
35
0
Order By: Relevance
“…Data from literature recorded on prickly pears stored under similar storage regimes also confirmed this trend. Specifically, Piga et al [11] verified that minimally processed fruit stored at 4 • C showed a weight loss threefold lower than fruit at 15 • C; the reduction in weight was very low, with a maximum of 0.66 g/100 g after 8 d at 15 • C. Similarly, in another paper also dealing with minimally processed cactus pear, Piga et al [42] verified that the reduction in weight was slight during the entire experiment, with a maximum of 0.15 g/100 g after 9 days at 4 • C. Liguori et al [22] verified that control samples of Opuntia ficus-indica samples showed a weight loss from 2 to 2.5 times higher than coated samples during cold storage, and differences between coated and uncoated fruit were significant starting from day 1 until the end of the cold storage period (9 days).…”
Section: Resultsmentioning
confidence: 86%
See 3 more Smart Citations
“…Data from literature recorded on prickly pears stored under similar storage regimes also confirmed this trend. Specifically, Piga et al [11] verified that minimally processed fruit stored at 4 • C showed a weight loss threefold lower than fruit at 15 • C; the reduction in weight was very low, with a maximum of 0.66 g/100 g after 8 d at 15 • C. Similarly, in another paper also dealing with minimally processed cactus pear, Piga et al [42] verified that the reduction in weight was slight during the entire experiment, with a maximum of 0.15 g/100 g after 9 days at 4 • C. Liguori et al [22] verified that control samples of Opuntia ficus-indica samples showed a weight loss from 2 to 2.5 times higher than coated samples during cold storage, and differences between coated and uncoated fruit were significant starting from day 1 until the end of the cold storage period (9 days).…”
Section: Resultsmentioning
confidence: 86%
“…Similarly, in another paper also dealing with minimally processed cactus pear, Piga et al [ 42 ] verified that the reduction in weight was slight during the entire experiment, with a maximum of 0.15 g/100 g after 9 days at 4 °C. Liguori et al [ 22 ] verified that control samples of Opuntia ficus-indica samples showed a weight loss from 2 to 2.5 times higher than coated samples during cold storage, and differences between coated and uncoated fruit were significant starting from day 1 until the end of the cold storage period (9 days).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among new postharvest management strategies of environment-friendly fresh fruit handling, the application of natural edible coatings has been reported to be very effective [7]. Edible coatings can act as a semipermeable barrier against gases and water vapor; can modify fruit tissue metabolism by affecting respiration rate, decreasing moisture and firmness loss, preserving the color, transporting antimicrobial, antioxidant, and other preservatives, controlling microbial growth, and maintaining fruit quality for a longer period [8].…”
Section: Introductionmentioning
confidence: 99%